The Alignment of Taxation and Sustainability : might the Digital Controls of Non-Financial Information Become a Universal Panacea? - Grau Ruiz, Maria Amparo (Review of European and Comparative Law, 2022)
There are certain trends that are already affecting –or will soon inevitably affect, the evolution of the tax law everywhere.These are the digitalization processes started by many tax administrations and the current challenges experienced by accounting and auditing institutions to provide reliable non-financial information. Both may offer new opportunities for fairer taxation in the search for sustainable development. In the middle of digital and green transformations, would it be possible to better adjust the tax treatment deserved by the taxpayers in accordance with their real impacts on sustainability? Regional and global organizations are devoting efforts to ensuring some degree of homogeneity in the measures to adopt. The purpose of the following pages is to open the discussions for in-depth research in the future. The dogmatic-legal and analytical methods have been used to supplement the comparative one in carrying out the review of the current state of the art and proposed changes.